Impact of centralization of services on outcomes in a rare tumour: Retroperitoneal sarcomas. Issue 2 (February 2019) - Kalaiselvan, R.; Malik, A.K.; Rao, R.; Wong, K.; Ali, N.; Griffin, M.; Chandrasekar, C.R.; Fenwick, S.F.; Poston, G.J.; Malik, H.
Abstract: Background and aim: The retroperitoneal tumor (RPT) service in the North West costal region of England was centralized in May 2011 by the merger of the Merseyside, Cheshire and Lancashire, Cumbria sarcoma networks. Our aim was to analyze the impact of centralization of services on patient outcomes. Methods: An analysis from 01/12/2004 to 30/11/2017 was undertaken from prospectively maintained database and electronic patient records; follow-up was until 30/04/2018. This time period encompassed 6.5 years before and after centralization of services took place. Survival analysis was done for Retroperitoneal Sarcomas (RPS) and also compared the impact of centralization. Results: 72 patients (27 men), median age 69 (21–90) years) underwent 95 operations with an intention to excise RPS. Overall there were 52 (54.7%) multi-visceral resections (MVR). 91/95 (95.8%) patients with primary tumors had surgery with a curative (R0/1) intent. 30-day and 90-day operative mortality was 3.2% (n = 3) and 4.2% (n = 4) respectively. The 5-year survival for patients undergoing resection for RPTs was 51.3%. 79 (83.1%) of the resections in this series occurred in the 6.5-years post-centralization with an increase in MVR between the two time points (p < 0.0006). Despite the more radical nature of surgery post-centralization, there was no difference in 5-year survival for RPS patients when compared to pre-centralization, p = 0.575. However the 5-yr survival post-centralization compared favorability to national outcomes. Conclusion: Centralization in the management of RPS has resulted in an increase in resection rates and more complex MVRs, without compromising R0/1 resection rates; peri-operative mortality or overall survival.